Analisa Ketepatan SIM Utilitas Lembur Terhadap Kegiatan Lembur Karyawan - Ahmad Sobari (Universitas Asahan, 2022)
Abstract - The website is an information technology that is growing rapidly at this time. Through the website, one can find the latest information in real time, which only requires a web browser application and an internet network. A building is designed using the Building Automation System (BAS) in order to facilitate building operations related to any existing equipment by operating automatically using a computer. In building operations, it certainly serves the companies in it and is also related to the facilities that will be enjoyed by employees. Overtime activities are routines that occur every day that are carried out by employees related to the work they do. Of course, there are, of course, some provisions in their implementation. The purpose of this research is to provide solutions related to the implementation procedures in employee overtime which are still in manual form or using paper. The research methodology that the author uses is the waterfall method, which is the initial approach of the Software Development Life Cycle (SDLC) that is used for application development. The development of the application that the author did through systematic stages, namely from the problem analysis stage, system design, coding stage, to the final stage, namely testing, The author uses the IDE Visual Code and uses the PHP programming language and MySQL as its database.Keywords - Overtime, Applications, and Websites